Spirituality Phenomenon and the Ideal-Realism Method in Modern Education - A. P. Vetoshkin (Образование и наука)
The paper is devoted to the spiritual revival of modern Russia. In the author’s view, the Russian Idea with its basic principles, moral, spiritual and semantic concepts should provide the guidelines for education, upbringing and the youth policy, guaranteeing the spiritual transformation and mobilization of the moral power for the benefit of the motherland, local society and family, as well as the personal growth. The theoretical and methodological bases for developing and implementing the above idea could be found in Russian national religious and philosophic thinking with its balanced dialectics of spiritual and social aspects. The experience of the ideal-realism, as the leading trend of the national spiritual culture, is being analyzed and summarized. The correlation between the ideal and material in social and individual life is demonstrated along with the dialectics and wholeness of the divine and human, religious and secular, ecclesiastical and civil.The author addresses the philosophic heritage of I. A. Ilyin, V. S. Solovyev, S. N. Trubetskoy, S. N. Bulgakov, N. A. Berdyayev, N. O. Losskiy etc, and regards spirituality as the basic defining, systematic and leading origin of the whole socio-historical process including human being formation and development, education and upbringing.